Anoreksi og agens: Kropsfilosofiske overvejelser om Cecilie Linds patografi Scarykost - Skiveren, Tobias (K&K - Kultur og Klasse, 2021)
Cultural studies and gender studies hold long-standing traditions for studying people with eating disorders as either passive objects subjected to misogynist discourses or subversive agents that negotiate societal norms. In both cases, agency is primarily investigated as a phenomenon that unfolds between the anorectic individual and the surrounding society. In contrast, this article explores how the question of agency also unfolds within the anorectic her-/himself. It does so by setting up a dialogue between the anorectic testimony of Cecilie Lind’s pathography Scarykost (2016) and philosophical ideas of corporeality in feminist new materialism, affect theory, and phenomenology. Ultimately, the article argues that the anorectic subject is not a homogenous individual that can easily be classified as either passive or active, but comprises an infra-corporeal landscape of social, psychic, and biological forms of agency that struggle to determine the will of the anorectic “I.” In that way, the article pushes back on the tendency in cultural and gender studies to make generalizing claims about the anorectic’s subversive agency – or lack thereof.